Clipless Laparoscopic Adrenalectomy in Children and Young Patients: A Single Center Experience with 12 Cases - Simforoosh, Nasser; Ahanian, Ali; Mirsadeghi, Amin; Lashay, Alireza; Hosseini Sharifi, Seyed Hossein; Soltani, Mohammad Hossein (Urology Journal, 2014)
Purpose: Laparoscopy is the gold standard approach for management of some adrenal masses in adult cases. Still there have not been many findings in case of children. We present our experience with clipless laparoscopic adrenalectomy in pediatric cases for the first time. Materials and Methods: From January 2007 to January 2011, thirteen laparoscopic adrenalectomy were performed in patients 5-18 years old. The first port (10 mm) was inserted using open approach above the umbilicus and three 5 mm trocars were inserted under direct vision. On the left side, the colon was mobilized medially, then the renal vein exposed. Adrenal vein was coagulated using bipolar cautery after separating from renal vein. No endoscopic clips were used. Results: Eight girls and five boys with the mean age of 14.4 years old (ranging from 5 to 18 years old) underwent laparoscopic adrenalectomy. The mean operative time was 151 ± 47 (80- 240) minutes. The mean size of adrenal lesions in greatest diameter was 6.9 ± 2.4 cm (3.5 to 10). The mean hospital stay was 3.7 days (2-5) and average follow-up time was 21 months (6-27). Conclusion: Laparoscopic adrenalectomy in children and young adults is effective and safe if the cases are selected appropriately. Clipless laparoscopic approach by an expert surgeon has acceptable outcomes.